2013
DOI: 10.1371/journal.pone.0059398
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Urinary 4-tert-Octylphenol Levels and Metabolism Enzyme Gene Variants on Idiopathic Male Infertility

Abstract: Octylphenol (OP) and Trichlorophenol (TCP) act as endocrine disruptors and have effects on male reproductive function. We studied the interactions between 4-tert-Octylphenol (4-t-OP), 4-n- Octylphenol (4-n-OP), 2,3,4-Trichlorophenol (2,3,4-TCP), 2,4,5-Trichlorophenol (2,4,5-TCP) urinary exposure levels and polymorphisms in selected xenobiotic metabolism enzyme genes among 589 idiopathic male infertile patients and 396 controls in a Han-Chinese population. Ultra high performance liquid chromatography-tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…A possible factor influencing the difference is that our study had a lower LOD (0.05 ng/mL) and higher percentage greater than the LOD (91.8%) than did the NHANES study (LOD = 0.2 ng/mL, percentage greater than the LOD, 57.4%), which would yield more precise percentiles and geometric means compared with studies with a higher LOD. Other studies have reported that the geometric mean 4-t-OP concentrations in the urine of Chinese men and women were 0.60 ng/mL and 0.90 ng/mL, respectively [ 12 , 25 ], which is similar to those of the Korean general population shown in this study.…”
Section: Discussionsupporting
confidence: 87%
“…A possible factor influencing the difference is that our study had a lower LOD (0.05 ng/mL) and higher percentage greater than the LOD (91.8%) than did the NHANES study (LOD = 0.2 ng/mL, percentage greater than the LOD, 57.4%), which would yield more precise percentiles and geometric means compared with studies with a higher LOD. Other studies have reported that the geometric mean 4-t-OP concentrations in the urine of Chinese men and women were 0.60 ng/mL and 0.90 ng/mL, respectively [ 12 , 25 ], which is similar to those of the Korean general population shown in this study.…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, alkylphenolic compounds have been linked to certain maternal exposures leading to health outcomes in their offspring,26–29 congenital heart defects,30 31 male infertility32 and certain types of neoplasms33–36 in epidemiological studies among humans. Studies have usually evaluated exposure to alkylphenols in urine samples26–28 32 35–37 or through occupational studies using JEMs 29–31 33 34. The evaluation of alkylphenolic compounds in epidemiological studies is hampered by limitations on the available laboratory tests to assess levels on blood serum or plasma samples, which are generally collected in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The level of sex hormones thus lowers and this produces menstrual irregularities and anovulation. In humans, moreover, it would appear that exposure to certain endocrine disruptors (4-tertoctylphenol) would alter the functionality of sperm [28]. In the literature emerges that research on idiopathic infertility is still incomplete.…”
Section: Discussionmentioning
confidence: 99%